Modeling and simulation of a quarter car model with a nonlinear damper - Shahimi, Sharis Shazzali; Ridhuan Siradj , Fadly Jashi Darsivan (IIUM, 2013)

(untitled)
An empirical investigation of a simple passenger quarter car model is presented. A differential equation of a quarter car model is carried out using MATLAB. Experiments are performed on a passive damper suspension to obtain the characteristics of a nonlinear damper, namely, the backbone of Force versus Velocity curves in which describes nonlinear effects that depend on varying frequencies and amplitudes of the road profile. The backbone is used to find the polynomial equations up to the order of 4 are applied. Results using the experimental parameters and the simulation models are obtained so that comparisons with respect to the performance of the damper are made. A road profile is then used to simulate a quarter car models using these nonlinear equations. Analysis of the results includes position, velocity, and acceleration of the sprung and unsprung masses of the model in a range of frequencies with respect to the input road profile.